Lowering Welfare Benefits: Intended and Unintended Consequences for Migrants and their Families - Lars Højsgaard Andersen; Christian Dustmann; Rasmus Landersø (Centre for Research & Analysis of Migration (CReAM), Department of Economics, University College London, 2019)
Denmark's Start Aid welfare reform reduced benefits to refugee immigrants by around 50 percent for those granted residency after the reform date. The reform led to a sharp short run increase in labor earnings and employment, but it also induced a strong female labor force withdrawal, and a large and persistent drop in disposable income for most households. Furthermore, the reform caused a sharp increase in property crime among both females and males. Moreover, children's likelihood of being enrolled in childcare or preschool, their performance in language tests, and their years of education all decreased, while teenagers' crime rates increased.
Keywords: E64; I30; J60; 330; Social assistance; welfare state; labor market outcomes; migration